FEASIBILITY OF DEVELOPING BANANA-COTTON FABRIC AS A SUSTAINABLE TEXTILE - K.SANGAMITHIRAI* (The Journal of Research ANGRAU, 2023)
Agro-based fibres for textiles are trying to substitute conventional fibres in some form as blending with other fibres or by themselves. Studies showed that fibres from banana pseudostem possess beneficial qualities that can be used for textiles. They are to be treated to carry out the spinning process and woven into a fabric as they possess considerable stiffness. Banana-cotton mixture or blended fabric is most suitable because both are cellulose in nature, and blending can be done homogeneously. The biodegradability of banana fibres and its availability as an agro waste can be considered as a sustainable source for textiles. This study conducted in the year 2019 attempted to find out the feasibility of using banana fibre to produce yarn and then weave it into fabric in an ecofriendly process. The woven material was evaluated for its physical properties. This could further be used for different end uses, can be produced on a larger scale and provide scope for the development of rural employment.